Exposure to di-2-ethylhexyl terephthalate in the U.S. general population from the 2015–2016 National Health and Nutrition Examination Survey. (February 2019) - Silva, Manori J.; Wong, Lee-Yang; Samandar, Ella; Preau, James L.; Jia, Lily T.; Calafat, Antonia M.
Abstract: Background: Di-2-ethylhexyl terephthalate (DEHTP) is used as a replacement plasticizer for other phthalates, including di-2-ethylhexyl phthalate (DEHP). Use of consumer products containing DEHTP may result in human exposure to DEHTP. Objective: To assess exposure to DEHTP in a nationally representative sample of the U.S. general population 3 years and older from the 2015–2016 National Health and Nutrition Examination Survey (NHANES). Method: We quantified two DEHTP metabolites, mono-2-ethyl-5-hydroxyhexyl terephthalate (MEHHTP) and mono-2-ethyl-5-carboxypentyl terephthalate (MECPTP) in 2970 urine samples by using online solid-phase extraction coupled with isotope dilution-high-performance liquid chromatography-tandem mass spectrometry. We used linear regression to examine associations between MEHHTP and MECTPP and several parameters including age, sex, race/ethnicity, and household income. We also compared the MEHHTP and MECPTP results to those of their corresponding DEHP metabolite analogs, namely mono-2-ethyl-5-hydroxyhexyl phthalate (MEHHP) and mono-2-ethyl-5-carboxypentyl phthalate (MECPP). Results: The weighted detection frequencies were 96% (MEHHTP) and 99.9% (MECPTP); urinary concentrations of the two metabolites correlated significantly (Pearson correlation coefficient = 0.89, p < 0.0001). MECPTP concentrations were higher than MEHHTP in all age, sex, race/ethnicity groups examined. Furthermore, MECPTP adjusted geometric mean (GM) concentrations were significantly higher in samples collected in the evening than in the morning or afternoon. Females had significantly higher adjusted GM concentrations of MEHHTP and MECPTP than males. We observed no significant associations between the adjusted GM concentrations of the metabolites and race/ethnicity. Both metabolite adjusted GM concentrations increased significantly with household income, and decreased significantly with age. Only household income was significantly associated with the concentrations of MECPP, but not of MEHHP, the two DEHP metabolites. The adjusted GM of the [MEHHTP]:[MECPTP] molar concentrations ratio increased with age, and was significantly higher in samples collected in the morning than in those collected in the afternoon or evening. Conclusions: Exposure to DEHTP is widespread in the U.S. general population 3 years and older. These data represent the first U.S. population-based representative background exposure to DEHTP. Highlights: Quantified two biomarkers of di-2-ethylhexyl terephthalate in the 2015–16 National Health and Nutrition Examination Survey Exposure to DEHTP is widespread in the U.S. general population 3 years and older These data represent the first nationally-representative background exposure to DEHTP in the United States